SCHOOL CHARACTERISTICS, SKILL COMPETENCY, SCHOOL IMAGES AND OF THE PARENTS SOCIAL CLASSES IN AFFECTING STUDENT DECISIONS TO CHOOSE MIDDLE VOCATIONAL SCHOOLS AT VOCATIONAL SCHOOLS IN PALANGKA RAYA CENTRAL KALIMANTAN - Lelo Sintani (Universitas Lambung Mangkurat, 2020)
This study was conducted to measure and analyze the effects of the School Characteristics, the Skill Competences, the Vocational School Image, and Parents’ Social Classes on the Students’ Preference in Selecting the Vocational Midle Schools in Palangka Raya. This study used a descriptive quantitative method. The population of this study was the Tenth Graders of Vocational Midle Schools Palangka Raya, specifically in the SMK Negeri 1 Palangka Raya, SMK Negeri 2 Palangka Raya, and SMK Negeri 3 Palangka Raya. To determine the number of the samples, Slovin Formula was applied. Data collection methods were obtained by interviewing the entitled and authorized parties who provided the data, through questioners by giving and distributing the questioners to the respondents (acted as the samples) who answered those questions, and the Study of documentation by collecting and studying the data relating to this study. The data that verify the assumptions were analyzed with Descriptive Analysis, Factor Analysis, and Multiple Regression Analysis. The result of the Descriptive Analysis concluded that the variables such as the school characteristics, the vocational skills offered, the school image, and the social classes of the parents were the important factors in students’ preference to continue their study in the vocational high school in Palangka Raya, Central Kalimantan. Thus, based on analyzing the confirmatory factors, each of question indicators of the variables was valid and reliable and indicators of each factor were accurate to measure those variables. The Multiple Regression Analysis indicates that based on the F-test, it was obtained that the school characteristics, the vocational skills offered, the school images, and the social classes of the parents affected simultaneously on the students’ preference in selecting the Vocational High School, and the value of the coefficient of determination shows that about 54.50% of the total variation of the students’ preference can be accounted for by the four variables. Moreover, the t-test result indicates partially that the variables of the school images and the vocational skills are significantly positive to influence the students’ preference in selecting the vocational school, which the variable of the school image is more dominant. However, the school characteristics and the parents social classes are not significantly affecting on the students’ preference to select the vocational school in Palangka Raya, Central Kalimantan.